#### Answer

s=$\frac{P-b}{2}$

#### Work Step by Step

P=2s+b
2s+b=P
2s=P-b
$\frac{2s}{2}$=$\frac{P-b}{2}$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

s=$\frac{P-b}{2}$

P=2s+b
2s+b=P
2s=P-b
$\frac{2s}{2}$=$\frac{P-b}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.